LTBI-negative close contacts of tuberculosis are more likely to develop the disease: enlightenment and lessons from a cluster outbreak - Du, Jingli; Su, Yue; Dong, Enjun; Qiao, Juan; Wang, Ruilan; Zhao, Wenjuan; Liang, Jianqin; Gong, Wenping (Frontiers in Public Health, 2023)
Background Tuberculosis (TB) prevention and control among groups living together, such as students, workers, older adults in nursing homes, and prisoners, present many challenges due to their particular age and environmental factors, which can make them more susceptible to TB clusters with significant societal impact. This study aimed to evaluate a TB cluster outbreak epidemic in a university and provide suggestions for improving TB control strategies for groups living together. Methods Pulmonary TB screening and close-contact investigation were conducted using acid-fast staining, sputum culture, GeneXpert testing, tuberculin skin testing (TST), interferon-gamma release assay (IGRA), and chest computed tomography (CT). GraphPad Prism 9.5.1 was utilized for data analysis. Collected epidemic data were comprehensively analyzed by rate comparison. Results The TB cluster outbreak epidemic was identified with an index case confirmed positive. The initial screening was conducted on potential close contacts of the index case, and the TST’s positive rate (diameter ≥ 5 mm) and strong positive rate (diameter ≥ 15 mm) among these close contacts were 65.60% (21/32) and 34.40% (11/32), respectively. Moreover, the latent TB infection (LTBI) rate (diameter ≥ 10 mm) was 43.75% (14/32), and the IGRA’s positive rate was 9.30% (3/32). Chest CT scans did not reveal any abnormalities. Surprisingly, 5 of the close contacts developed active TB in the second screening, accompanied by changes from negative to positive TST and/or IGRA results, after 3 months of follow-up. Accordingly, we expanded the screening scope to include another 28 general contacts. We found that the positive rate (78.00%, 25/32), strong positive rate (50.00%, 16/32), and LTBI rate (62.50%, 20/32) of the 32 close contacts were significantly higher than those of the additional general contacts (28.00%, 8/28; 14.3%, 4/28; 25.00%, 7/28), as indicated by p < 0.05. Conclusion In the event of an epidemic TB outbreak, it is essential to rapidly identify the source of infection and initiate timely screening of close contacts. The initial screening should be focused on individuals without LTBI, who are at higher risk of developing TB. In purified protein derivative-negative individuals living in groups, additional vaccination or revaccination with Bacille Calmette-Guérin may help prevent cluster outbreaks of TB.